2016
DOI: 10.1371/journal.pone.0165475
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Irreversible Electroporation Protocols for In-vivo Myocardial Decellularization

Abstract: BackgroundIrreversible electroporation (IRE) is a non-thermal cell ablation approach that induces selective damage to cell membranes only. The purpose of the current study was to evaluate and optimize its use for in-vivo myocardial decellularization.MethodsForty-two Sprague-Dawley rats were used to compare myocardial damage of seven different IRE protocols with anterior myocardial infarction damage. An in-vivo open thoracotomy model was used, with two-needle electrodes in the anterior ventricular wall. IRE pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…notably compared different protocols, observing that longer pulse duration, multiple pulses, higher current voltage, and lower interpulse distance were associated with bigger tissue damage. They also observed a key feature of IRE, which resides in sparing the extracellular structures …”
Section: Application Of Ire In Cardiologymentioning
confidence: 98%
See 1 more Smart Citation
“…notably compared different protocols, observing that longer pulse duration, multiple pulses, higher current voltage, and lower interpulse distance were associated with bigger tissue damage. They also observed a key feature of IRE, which resides in sparing the extracellular structures …”
Section: Application Of Ire In Cardiologymentioning
confidence: 98%
“…Furthermore, safety issues concerning the formation of gas bubbles during applications must be considered, due to the long duration of defibrillation pulses (6–10 ms). IRE DC‐PEFs can be generated also by benchmark programmable electroporators for molecular biology, such as BTX ECM 830 (Harvard Apparatus) square wave pulse generator . Commercial dedicated IRE DC pulse generator is for now represented only by the Nanoknife ® system (HVP‐01 Electroporation System, Angiodynamics).…”
Section: Application Of Ire In Cardiologymentioning
confidence: 99%
“…Hypotonic treatment has been reported to cause minimal ECM damage . Other physical techniques which have also been reported to assist in cell lysis include sonication and electroporation which exert their effect by disrupting cell membranes …”
Section: Ecm Decellularization Techniquesmentioning
confidence: 99%
“…Zager [85] meticulously evaluated for a graded effect of different electroporation protocols on in vivo myocardial tissue. Results from their study showed IRE has a graded effect on the myocardium and that the extent of ablation can be controlled by changing pulse length, frequency and number, as well as by changing electric field intensity.…”
Section: Cardiac Tissuementioning
confidence: 99%